A review of uncertainties in atmospheric modeling of mercury chemistry I. Uncertainties in existing kinetic parameters – Fundamental limitations and the importance of heterogeneous chemistry - Subir, Mahamud; Ariya, Parisa A.; Dastoor, Ashu P. (Atmospheric environment (1994), 2011)
Mercury and its related compounds are widely recognized as global pollutants. The accurate atmospheric modeling of its transport and fate has been the subject of much research throughout the last decade. Atmospheric gas, aqueous and heterogeneous chemistry are expected to occur for Hg-containing species and accurate implementation of their chemical parameters is essential for realistic modeling of mercury cycling. Although significant progress has been made, the current state of knowledge of mercury chemistry exhibits numerous uncertainties. The objective of this two-part review is to explore the sources of uncertainty from the viewpoint of mercury chemistry. In this first part, we assess the discrepancy that exists in the currently available mercury kinetic parameters for the gas and aqueous phases. Theoretical and experimental approaches of rate constant determination exhibit various levels of limitation and accuracy. We present an overview of the available techniques and the assumptions and shortcomings associated with these methods in order to assist the atmospheric modellers. We review specific mercury oxidation and reduction reactions that have been investigated and are commonly implemented in mercury models with respect to the uncertainties associated with them. We reveal that for most of these mercury reactions our current state of knowledge reflects a lack of proper understanding of their mechanisms. Atmospheric heterogeneity is a topic of great importance and we elaborate upon it in part II of this review. ► We assess discrepancies in the existing mercury gas and aqueous phase rate constants. ► Assumptions in experimental and theoretical methods of rate determination are discussed. ► Uncertainties for specific mercury redox reactions are evaluated. ► Our current state of knowledge lacks proper understanding of most mercury reaction mechanisms. ► The available rate constants are not realistic due to atmospheric heterogeneity.